Pulmonary artery hypertension patients and the coronavirus disease of 2019 (COVID-19): are they protected from severe disease? - Anggoro Budi Hartopo; Dyah Wulan Anggrahini; Bambang Budi Siswanto; Lucia Kris Dinarti (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2020)
The coronavirus disease of 2019 (COVID-19) is a current pandemic of viral infection which mainly involves respiratory system and may progress into severe multiple organ dysfunction and mortality. Pulmonary artery hypertension (PAH) is a disease marked by increased mean pulmonary artery pressure and pulmonary vascular resistance due to pulmonary panvascular remodeling. Although rare, the prevalence of PAH is currently escalating in Indonesia due to increased diagnostic capacity and referral, treatment availability and improved survival. Despite chronic cardiac and pulmonary diseases are at increased risk to develop severe COVID-19, patients with PAH are considered to be not in higher risk to develop severe COVID-19. However, whether this population is protected from severe COVID-19 is unclear. There are protective and offensive factors need to be considered in PAH patients in respect to COVID-19.